Avaliação da eficiência de fungos entomopatogênicos no controle biológico de Glycaspis brimblecombei Moore, 1964 (Hemiptera: psyllidae) - Carnielli, Thayanne Loer (2018)
Eucalyptus plantations are affected by native and exotic pests. The latter can cause greater damage, leading to economic losses due to the lack of local natural enemies to control the population. Among the pests that attack eucalyptus plantations, the insect Glycaspis brimblecombei Moore (Hemiptera: Psyllidae), known as Eucalyptus redgum lerp psyllid, was first detected in Brazil in 2003, in the state of São Paulo. The insect damaged eucalyptus plantations, causing die-back and reduction in the photosynthetic activity. Synthetic chemical formulations have been used to control this insect; however, a new solution should be developed since these formulations are toxic and harmful to the human health and environment. Entomopathogenic fungi can be used as an alternative control method. The present study aimed to evaluate the efficiency of entomopathogenic fungi as a biological control method for G. brimblecombei, both in the laboratory and in commercial eucalyptus plantations. The laboratory trial used five entomopathogenic fungi isolates (Isaria fumosorosea, Beauveria bassiana, Metarhizium robertsii, and Metarhizium anisopliae) and a control treatment, with a seven-day evaluation period. The field trial used two fungi (I. fumosorosea and B. bassiana, from the germplasm bank of Embrapa Coastal Tablelands), two commercial fungi (Boveril and Metarril, which are commercial products formulated using conidia from the fungi B. bassiana and M. anisopliae), a chemical insecticide (composed of Bifenthrin), and a control treatment (water + spreader sticker), with a three-day evaluation period. The isolates used in the field and under controlled conditions were replicated in Petri dishes and kept in a B.O.D. at 26 ± 10%, with a 12-hour photoperiod. Pathogenicity analyses were performed to determine the most efficient isolates in the mortality of G. brimblecombei. The mortality of G. brimblecombei differed between treatments whose fungi isolates were kept in the laboratory; M. robertsii presented the best result, with 100% population reduction in two days. Regarding the field trial, treatments I. fumosorosea and B. bassiana had the best results, with an 83.56% and 51.53% population reduction, respectively, in less than three days. The fungi I. fumosorosea, B. bassiana, M. robertsii, and M. anisopliae showed satisfactory results for the efficient control of G. brimblecombei in the field and under controlled conditions. Therefore, these fungi are a potentially viable alternative for use in Integrated Management Programs of G. brimblecombei.